Neurocognitive Impairment and HIV Risk Factors: A Reciprocal Relationship - Anand, Pria (2010)
Cognitive impairment among populations at risk for HIV poses a significant barrier to managing risk behaviors. The impact of HIV and several cofactors, including substance abuse and mental illness, on cognitive function is discussed in the context of HIV risk behaviors, medication adherence, and risk-reduction interventions. Literature suggests that cognitive impairment is intertwined in a close, reciprocal relationship with both risk behaviors and medication adherence. Not only do increased risk behaviors and suboptimal adherence exacerbate cognitive impairment, but cognitive impairment also reduces the effectiveness of interventions aimed at optimizing medication adherence and reducing risk. In order to be effective, risk-reduction interventions must therefore take into account the impact of cognitive impairment on learning and behavior.